P071 Police harassment and HIV/STI risk behaviors among a sample of people who inject drugs on the U.S.-mexico border. (14th July 2019) - Beltran, Oscar; Lechuga, Julia; Perez, Gilberto; Ramos, Rebeca; Rodriguez, Maria Ramos
Abstract : Background: The number of people who inject drugs on the U.S.-Mexico border has been increasing over the last years and has become a public health concern due to their vulnerability to HIV and other sexually transmitted infections (STIs). We explored the HIV/STI risk behaviors of people who inject drugs (PID) and their relationship to police harassment. Methods: The sample for this study included 200 PID (75% male, 25% female) recruited through respondent driven sampling methodology. Data analysis was conducted using SPSS v.25; independent sample t-test was used to identify mean differences across PID experiencing police harassment during the past three months vs. PID who did not experience police harassment in the last three months; chi-squared analysis was used to explore proportional differences on substance use and HIV/STIs sexual risk behaviors. Results: Overall, 1.9% of participants reported being diagnosed with HIV, and 23.3% with hepatitis C. PID who experienced police harassment reported higher use of other drugs: marijuana (OR=1.78, 95%CI=[1.05, 3.04], p=0.015), inhalants (OR=2.06, 95%CI=[1.40, 3.03], p<0.001), cocaine (OR=1.78, 95%CI=[1.14, 2.80], p<0.01), crystal (OR=2.11, 95%CI=[1.27, 3.52], p<0.01), methamphetamines (OR=2.06, 95%CI=[1.22, 3.48], p<0.01), tranquilizers (OR=2.02, 95%CI=[1.35, 3.02], p<0.001). Regarding risk behaviors, PID who experience police harassment reported higher numbers of sex partners (Mean: 10.99 vs. 5.72, p=0.024) and condom-less sex (Mean: 3.18 vs. 1.55, p=0.042). Men reported higher rates of sex with other men (OR=1.66, 95%CI=[1.25, 2.19], p<0.01). More PID reported being gang raped (OR=2.15, 95%CI=[1.73, 2.68], p<0.001) and having condom-less sex with a person known to have HIV (OR=1.48, 95%CI=[1.10, 1.99], p<0.01). Conclusion: There is a clear relationship between experiencing police harassment, engaging in HIV high-risk behaviors, and higher consumption of other drugs among PID. Understanding the structural dynamics of discrimination and stigma among this group (e.g. double stigma, being MSM) could lead to a deeper understanding of these relationships. Disclosure: No significant relationships.